1
$\begingroup$

$x$, $y$ and $z$ are positives such that $x + 2y + 3z = 2$. Calculate the maximum value of $$ \sqrt{\frac{3yz}{3yz + x}} + \sqrt{\frac{3zx}{3zx + 4y}} + \sqrt{\frac{xy}{xy + 3z}}$$

This problem is brought to you by a recent competition. There should be different answers that are more creative than the one I have provided. Oh well...

$\endgroup$
  • 1
    $\begingroup$ Try not to use \dfrac or \displaystyle in titles. $\endgroup$ – StubbornAtom Jun 11 at 7:23
1
$\begingroup$

Let $x=\frac{2}{3}a$, $y=\frac{1}{3}b$ and $z=\frac{2}{9}c$.

Thus, $a+b+c=3$ and by AM-GM we obtain: $$\sqrt{\frac{3yz}{3yz + x}} + \sqrt{\frac{3zx}{3zx + 4y}} + \sqrt{\frac{xy}{xy + 3z}}=\sum_{cyc}\sqrt{\frac{bc}{bc+3a}}=$$ $$=\sum_{cyc}\sqrt{\frac{bc}{(a+b)(a+c)}}\leq\frac{1}{2}\sum_{cyc}\left(\frac{b}{a+b}+\frac{c}{a+c}\right)=\frac{1}{2}\sum_{cyc}\left(\frac{b}{a+b}+\frac{a}{b+a}\right)=\frac{3}{2}.$$ The equality occurs for $a=b=c=1$, which says that we got a maximal value.

$\endgroup$
0
$\begingroup$

We have that

$$\sqrt{\frac{3yz}{3yz + x}} + \sqrt{\frac{3zx}{3zx + 4y}} + \sqrt{\frac{xy}{xy + 3z}}$$

$$ = \sqrt{\frac{3yz}{3yz + (2 - 2y - 3z)}} + \sqrt{\frac{3zx}{3zx + 2(2 - 3z - x)}} + \sqrt{\frac{xy}{xy + (2 - x - 2y)}}$$

$$ = \sqrt{\frac{3yz}{(1 - y)(2 - 3z)}} + \sqrt{\frac{3zx}{(2 - 3z)(2 - x)}} + \sqrt{\frac{xy}{(2 - x)(1 - y)}}$$

$$\le \frac{1}{2}\left(\frac{2y}{2 - 3z} + \frac{3z}{2 - 2y}\right) + \frac{1}{2}\left(\frac{3z}{2 - x} + \frac{x}{2 - 3z}\right) + \frac{1}{2}\left(\frac{x}{2 - 2y} + \frac{2y}{2 - x}\right)$$

$$ = \frac{1}{2}\left(\frac{2y + 3z}{2 - x} + \frac{3z + x}{2 - 2y} + \frac{x + 2y}{2 - 3z}\right)$$

$$ = \frac{1}{2}\left[(x + 2y + 3z - 2)\left(\frac{1}{2 - x} + \frac{1}{2 - 2y} + \frac{1}{2 - 3z}\right) - 3\right] = \frac{3}{2}$$

The equality sign occurs when $\left\{ \begin{align} x(2 - x) = 2y(2 - 2y) = 3z(2 - 3z)\\ x + 2y + 3z = 2\end{align} \right.$

$\iff \left\{ \begin{align} (x - 1)^2 = (2y - 1)^2 = (3z - 1)^2\\ x + 2y + 3z = 2 \end{align} \right.$$\implies x = 2y = 3z = \dfrac{x + 2y + 3z}{1 + 1 + 1} = \dfrac{2}{3}$

$\iff (x, y, z) = \left(\dfrac{2}{3}, \dfrac{1}{3}, \dfrac{2}{9}\right)$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.